2016
DOI: 10.1007/s10995-016-1942-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Preterm Care at the Facility Level: Stakeholder Qualitative Study in Central and Southern Malawi

Abstract: Objectives Malawi is estimated to have one of the highest preterm birth rates in the world. However, care of preterm infants at facility level in Malawi has not been explored. We aimed to explore the views of health stakeholders about the care of preterm infants in health facilities and the existence of any policy protocol documents guiding the delivery of care to these infants. Methods We conducted 16 in-depth interviews with health stakeholders (11 service providers and 5 policy makers) using an interview gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Study participants highlighted that having a dedicated KMC ward facilitated the practice, which is aligned with other studies in sub-Saharan Africa that described insufficient space as a critical challenge [19,26,28,29,35,36]. However, beyond a sufficient space, there is a need for family-centered care to support mothers and their companions during their extended stay at the hospital.…”
Section: Investment In Basic Needssupporting
confidence: 69%
See 1 more Smart Citation
“…Study participants highlighted that having a dedicated KMC ward facilitated the practice, which is aligned with other studies in sub-Saharan Africa that described insufficient space as a critical challenge [19,26,28,29,35,36]. However, beyond a sufficient space, there is a need for family-centered care to support mothers and their companions during their extended stay at the hospital.…”
Section: Investment In Basic Needssupporting
confidence: 69%
“…Participants in this study highlighted the multiple roles that nurse midwives played from counselling caregivers on initiation to being the main medical provider monitoring infants during KMC as well as supporting labour, delivery and nursery wards during emergencies. The challenge of adequate staffing and workload especially during night, weekend and holiday shifts has been reported in studies in sub-Saharan Africa as a key barrier to KMC practice [17,18,21,[24][25][26][27][28][29][30][31]. Investments in staffing can help to move beyond basic practice of initiating and educating caregivers on danger signs to continued support.…”
Section: Investment In Staffingmentioning
confidence: 99%
“…However, the findings of this study revealed that there was lack of adequate radiant warmers, incubators and KMC rooms were overcrowded. Insufficient KMC rooms is common in most low income countries [26]. Preterm babies were found to be suffering from RDS which is a condition related to prematurity and accounts for 15% morbidity in infants born at 34 weeks and 3.2% in those born at 36 weeks [22].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Previous studies in developing countries such as Uganda [ 38 ], Ethiopia [ 39 ] and Ghana [ 40 ] have shown that government or hospital investments aimed at improving the privacy and comfort of the delivery environment have improved KMC implementation. With regards to labour resources, uneven and inadequate regional allocation of medical staff may negatively affect KMC implementation [ 41 , 42 ]. As for equipment, ensuring the supply of standardised, safe and comfortable equipment and consumables can enhance parental compliance with KMC implementation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%